Technology readiness and technology acceptance in virtual reality tourism: An integration of TOE and TAM frameworks - Tuyen Tran; Nguyen Thi Van Hanh (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2025)
Virtual reality (VR) tourism presents a creative way to improve travel experiences and offers smart travel. On the other hand, compared to wealthy nations with sophisticated information infrastructure and smart tourism support, the exploitation of VR tourism in emerging tourism economies looks to be limited. Focusing on Ho Chi Minh City, Vietnam, a case study for growing tourism businesses, this paper attempts to establish a model identifying elements involving VR tourism acceptance in developing markets. Expanding the Technology Acceptance Model (TAM) with the Technology, Organization, and Environment (TOE) framework helps this model to emphasize elements like organizational readiness and knowledge of VR tourism in developing countries. Using partial least squares structural equation modeling (PLS-SEM) on data set of 260 tourism companies, the results show that perceived ease of use is less important, perceived usefulness of VR tourism has the largest effect on adoption intentions. Policy variables have little effect; critical elements are technological developments and organizational ability, compatibility. Therefore, in growing tourism industries, innovation, usefulness and availability of VR tourism play the most significant role. These findings suggest theoretical and practical implications on VR tourism adoption in developing markets.
Keywords: 330; Virtual reality tourism; technology acceptance model (TAM); technology; organization and environment (TOE) framework; tourism enterprises